Additive capable of improving oxidation resistance of ultrathin copper foil and copper foil produced by additive
By adding additives such as ytterbium ions, dibutyl hydroxytoluene, polyethylene glycol and brightener to the electrolyte, electrolyzing copper foils solves the problem that the prior art is difficult to prevent oxidation of copper foils in high temperature and high humidity environments, and achieves an efficient antioxidant effect.
Patent Information
- Application Number
- CN202411883755.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-11
AI Technical Summary
The existing copper foil anti-oxidation treatment technology is difficult to effectively prevent copper foil oxidation in high temperature and high humidity environments, affecting the performance and life of lithium batteries.
The copper foil is electrolyzed by adding additives of components such as ytterbium ions, dibutyl hydroxytoluene, polyethylene glycol and brightener to the electrolyte to form a copper foil with high oxidation resistance.
The 6μm ultra-thin copper foil was placed at 85℃ and 85% relative humidity for 120 hours without oxidation and discoloration, and baked at 230℃ for 60 minutes without oxidation and discoloration, which significantly improved the anti-oxidation performance of the copper foil.
Smart Images

Figure CN119800459A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-oxidation treatment of copper foil, and particularly relates to an additive capable of improving the anti-oxidation property of ultra-thin copper foil and the copper foil produced therefrom. Background Art
[0002] Ultra-thin copper foil is one of the important cathode materials for lithium batteries. It is difficult to completely isolate it from air during storage and application. The oxygen and water vapor in the air will react with the copper foil to form a layer of copper oxide film on the surface of the copper foil, which will increase the internal resistance of the battery and reduce the battery capacity, affecting the performance and life of the battery. Therefore, it is extremely important to carry out anti-oxidation treatment on the electrolytic copper foil.
[0003] The existing anti-oxidation treatment of copper foil mainly starts with the surface treatment process, electroplating a metal layer containing chromium or nickel on the surface of the copper foil to form a passivation layer on the surface of the copper foil, thereby isolating the air and achieving the purpose of anti-oxidation. Similarly, some inventors have abandoned the chromium plating process to achieve the anti-oxidation function. For example, Chinese patent application 201911389892.8 does not use the existing chromium plating passivation process, but uses cerium nitrate and myristic acid as raw materials, and performs electrodeposition in the presence of gluconic acid to generate a uniform Ce(CH3(CH2) on the surface of the copper foil. 12 COO)4 film layer to achieve anti-oxidation. This formula is relatively complex and it is difficult to stably control its components in actual production. In addition, there is also the method of improving the antioxidant properties by coating the surface with organic silicon compounds. For example, Chinese patent application 202410275399.8 improves the antioxidant properties of ultra-thin copper foil by vacuum coating a layer of aminosilane on the surface of the copper foil. In this patent, only the antioxidant properties of the silane-coated and non-silane-coated foils are compared, and it is not compared with the existing passivation chromium plating technology. Moreover, it only achieves the level of maintaining no discoloration for 15 minutes at 140°C. With the development of the lithium battery industry, the requirements for electric heating peak values are also higher. During the application process, the temperature of the copper foil may exceed 140°C, so it is also necessary to bake at a higher temperature to determine the antioxidant properties.
[0004] Existing anti-oxidation treatments for copper foil also include improvements from electrolytic additives, such as Chinese patent application 202410774465.6. In this patent, there are 7 additive components with a relatively complex formula, and the final product can withstand 145°C for 20 minutes without being oxidized. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide an additive that can improve the antioxidant properties of ultra-thin copper foil and the copper foil produced therefrom. By adding the additive to the electrolyte to electrolyze the copper foil, it can be achieved that the 6μm ultra-thin copper foil has no oxidative discoloration when placed at 85°C and 85% relative humidity for 120 hours, and has no oxidative discoloration after being baked at 230°C for 60 minutes.
[0006] The invention provides an additive capable of improving the oxidation resistance of an ultra-thin copper foil. The additive comprises ytterbium ions, dibutyl hydroxytoluene, polyethylene glycol and a brightener.
[0007] Preferably, the ytterbium ions include one or more of ytterbium sulfate, ytterbium nitrate or other salts containing ytterbium ions.
[0008] Preferably, the polyethylene glycol includes one or more of polyethylene glycol 1000, polyethylene glycol 2000 or polyethylene glycols with other molecular weights.
[0009] Preferably, the brightener includes one or more of sodium polydisulfide propane sulfonate, sodium isothiourea propane sulfonate, and sodium imidazole dithiocarboxylate propane sulfonate.
[0010] Preferably, the ytterbium ion concentration is 2.0-5.0 mg / L, and the butylated hydroxytoluene concentration is 10.0-20.0 mg / L.
[0011] Preferably, the concentration of polyethylene glycol is 2.0 to 20.0 mg / L, and the concentration of brightener is 5.0 to 20.0 mg / L.
[0012] The present invention also provides a copper foil capable of improving the oxidation resistance of the ultra-thin copper foil, wherein the copper foil has no oxidative discoloration when placed at 85° C. and 85% relative humidity for 120 hours and has no oxidative discoloration after being baked at 230° C. for 60 minutes.
[0013] Preferably, the method comprises the following steps:
[0014] (1) Preparation of additives;
[0015] (2) adding the additive to the copper sulfate electrolyte, mixing and stirring evenly, and then electrolyzing and producing foil;
[0016] (3) The obtained copper foil is passivated with chromic anhydride passivation solution, and then dried and peeled to obtain the finished copper foil.
[0017] Preferably, the copper ion concentration in the copper sulfate electrolyte in step (2) is controlled at 80-110 g / L, the acid concentration is controlled at 90-130 g / L, the chloride ion concentration is controlled at 5-20 mg / L, the electrolyte temperature is controlled at 45-60° C., and the current density is controlled at 40-60 A / dm 2 .
[0018] Preferably, the test method for the oxidation resistance of the copper foil includes a double 85 oxidation resistance test and a high temperature oxidation resistance test.
[0019] The double 85 oxidation resistance test method is: place the copper foil in a constant temperature and humidity chamber, set the temperature to 85°C, set the humidity to 85%, leave it for 72 hours and 120 hours, and observe whether the copper foil is oxidized and discolored. The high temperature oxidation resistance test method is: place the copper foil in an oven, set the oven temperature to 230°C, leave it for 30 minutes and 60 minutes, and observe whether the copper foil is oxidized and discolored. The high temperature tensile elongation test method is tested according to 7.1 of GB / T 29847-2013.
[0020] Ytterbium ions are added to the additive of the present invention. Ytterbium ions can be adsorbed at the grain boundary during copper electrolytic deposition, play a pinning role, inhibit copper grain growth, and then reduce the pores between grains, improve surface quality, make oxygen molecules more difficult to adsorb on the surface of copper foil, thereby improving oxidation resistance, and at the same time, the dosage is small, and it is not easy to cause defects between grains; butylated hydroxytoluene can form antioxidant free radicals on the surface of copper foil, preferentially combine with oxygen molecules to form stable compounds, and play a role in protecting copper foil. During the electrolysis process, ytterbium ions can synergize with butylated hydroxytoluene. Ytterbium ions reduce the adsorption of oxygen molecules on the surface of copper foil by improving the surface quality. However, when oxygen molecules are still adsorbed on the surface, oxygen molecules will also preferentially combine with the antioxidant free radicals of butylated hydroxytoluene to form stable compounds, thereby protecting copper foil from the inside out to improve oxidation resistance. However, when the amount of butylated hydroxytoluene added is too much, the antioxidant free radicals distributed on the surface will agglomerate and reduce the efficiency of its adsorption of oxygen molecules, and the oxidation resistance of copper foil will deteriorate instead. Therefore, it is necessary to control the content of butylated hydroxytoluene. At the same time, polyethylene glycol is used as an inhibitor to reduce the difference between high and low currents during copper ion deposition, allowing copper to be deposited evenly; sodium polydisulfide dipropane sulfonate is used as a brightener to reduce the conversion energy of copper ions into copper grains, promote nucleation, and increase the deposition rate of copper. The interaction between the two provides a guarantee for normal electrolytic foil production.
[0021] The present invention introduces a double 85 oxidation resistance test method. Since copper foil will be exposed to oxygen and water vapor in the air during transportation, processing and application, the previous anti-oxidation test method only focuses on the influence of temperature, that is, the anti-oxidation performance is judged to be qualified only if there is no color change after being placed at a certain high temperature for a period of time, and basically pays no attention to the influence of water vapor; while the test method of the present invention not only pays attention to the temperature but also considers the influence of water vapor on the oxidation of copper foil, and the judgment method is more comprehensive.
[0022] Beneficial Effects
[0023] The additive of the present invention has a simple formula, a small number of components, and an easy-to-control process. By adding the additive to the electrolyte to electrolyze copper foil, the 6μm ultra-thin copper foil can be placed at 85°C and 85% relative humidity for 120 hours without oxidative discoloration, and baked at 230°C for 60 minutes without oxidative discoloration. When the additive does not contain the two components of ytterbium ions and butylated hydroxytoluene, the produced 6μm ultra-thin copper foil is placed at 85°C and 85% relative humidity for 72 hours without oxidative discoloration, but is moderately oxidized to purple-red after being placed for 120 hours, is slightly oxidized to light orange after being baked at 230°C for 30 minutes, and is moderately oxidized to purple-red after being baked for 60 minutes. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the result of high temperature baking at 230°C for 60 minutes in Experimental Example 1.
[0025] Figure 2 This is the result of baking at 230°C for 30 minutes in Comparative Example 3.
[0026] Figure 3 This is the result of baking at 230°C for 60 minutes in Comparative Example 3. DETAILED DESCRIPTION
[0027] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0028] Example 1
[0029] Copper sulfate pentahydrate, concentrated sulfuric acid, deionized water and dilute hydrochloric acid are prepared into an electrolyte and introduced into an electrolytic cell with a heating and temperature control function. The prepared additive solution is added into the electrolyte and mixed and stirred evenly. After the electrolyte in the electrolytic cell is heated to 55°C by the heating and temperature control system, electroplating begins. The current density is 50A / dm 2 After electrolytic production, the copper foil is passivated with chromic anhydride passivation solution, and then dried and peeled to obtain a 6μm finished copper foil.
[0030] The electrolyte has a copper ion concentration of 90 g / L, an acid content of 110 g / L, and a chloride ion concentration of 15 mg / L. The additives include ytterbium sulfate: 2 mg / L, butylated hydroxytoluene: 8 mg / L, polyethylene glycol 1000: 10 mg / L, and sodium polydisulfide dipropane sulfonate: 15 mg / L.
[0031] Example 2
[0032] Copper sulfate pentahydrate, concentrated sulfuric acid, deionized water and dilute hydrochloric acid are prepared into an electrolyte and introduced into an electrolytic cell with a heating and temperature control function. The prepared additive solution is added into the electrolyte and mixed and stirred evenly. After the electrolyte in the electrolytic cell is heated to 55°C by the heating and temperature control system, electroplating begins. The current density is 50A / dm 2 After the electrolytic copper foil is produced, the copper foil is passivated by chromic anhydride passivation solution to obtain a 6μm finished copper foil.
[0033] The electrolyte has a copper ion concentration of 90 g / L, an acid content of 110 g / L, and a chloride ion concentration of 15 mg / L. The additives include 4 mg / L ytterbium sulfate, 8 mg / L butylated hydroxytoluene, 10 mg / L polyethylene glycol 1000, and 15 mg / L sodium polydisulfide dipropane sulfonate.
[0034] Example 3
[0035] Copper sulfate pentahydrate, concentrated sulfuric acid, deionized water and dilute hydrochloric acid are prepared into an electrolyte and introduced into an electrolytic cell with a heating and temperature control function. The prepared additive solution is added into the electrolyte and mixed and stirred evenly. After the electrolyte in the electrolytic cell is heated to 55°C by the heating and temperature control system, electroplating begins. The current density is 50A / dm 2 After the electrolytic copper foil is produced, the copper foil is passivated by chromic anhydride passivation solution to obtain a 6μm finished copper foil.
[0036] The electrolyte has a copper ion concentration of 90 g / L, an acid content of 110 g / L, and a chloride ion concentration of 15 mg / L. The additives include ytterbium sulfate: 2 mg / L, butylated hydroxytoluene: 15 mg / L, polyethylene glycol 1000: 10 mg / L, and sodium polydisulfide dipropane sulfonate: 15 mg / L.
[0037] Example 4
[0038] Copper sulfate pentahydrate, concentrated sulfuric acid, deionized water and dilute hydrochloric acid are prepared into an electrolyte and introduced into an electrolytic cell with a heating and temperature control function. The prepared additive solution is added into the electrolyte and mixed and stirred evenly. After the electrolyte in the electrolytic cell is heated to 55°C by the heating and temperature control system, electroplating begins. The current density is 50A / dm 2 After the electrolytic copper foil is produced, the copper foil is passivated by chromic anhydride passivation solution to obtain a 6μm finished copper foil.
[0039] The electrolyte has a copper ion concentration of 90 g / L, an acid content of 110 g / L, and a chloride ion concentration of 15 mg / L. The additives include ytterbium sulfate: 2 mg / L, butylated hydroxytoluene: 15 mg / L, polyethylene glycol 1000: 5 mg / L, and sodium polydisulfide dipropane sulfonate: 15 mg / L.
[0040] Comparative Example 1
[0041] The only difference from Experimental Example 1 is that butylated hydroxytoluene is not added to the additive, the contents of other components remain unchanged, and the experiment is carried out according to the same process as Experimental Example 1.
[0042] Comparative Example 2
[0043] The only difference from Experimental Example 1 is that ytterbium sulfate is not added to the additive, the contents of other components remain unchanged, and the experiment is carried out according to the same process as Experimental Example 1.
[0044] Comparative Example 3
[0045] The only difference from Experimental Example 1 is that ytterbium sulfate and butylated hydroxytoluene are not added to the additive, the contents of other components remain unchanged, and the experiment is carried out according to the same process as Experimental Example 1.
[0046] Comparative Example 4
[0047] The only difference from Experimental Example 1 is that the content of butylated hydroxytoluene in the additive is 35 mg / L, the contents of other components remain unchanged, and the experiment is carried out according to the same process as Experimental Example 1.
[0048] In order to understand this experiment more intuitively, the concentrations of each component in the experimental examples and comparative examples are given in a tabular form, as shown in Table 1.
[0049] Table 1 Concentration of each component in experimental examples and comparative examples
[0050]
[0051] The test results of the experimental example and the comparative example are shown in Table 2.
[0052] Table 2 Experimental examples and comparative test results
[0053]
[0054] From the results in Table 2, it can be seen that Examples 1, 2, 3 and 4 can be placed at 85°C and 85% relative humidity for 120 hours without oxidative discoloration, and after being baked at 230°C for 60 minutes, there is no oxidative discoloration. Comparative Examples 1, 2 and 4 do not change color after being placed at 85°C and 85% relative humidity for 72 hours, but are slightly oxidized and discolored into light orange after being placed for 120 hours, and Comparative Example 3 is moderately oxidized and becomes purple-red after being placed for 120 hours.
[0055] Example 1, Example 2, Example 3, and Example 4 were baked at 230°C for 60 minutes without oxidative discoloration. Figure 1As shown. Comparative Examples 1, 2, and 4 were not oxidized and discolored after being baked at 230°C for 30 minutes, but were slightly oxidized and discolored to light orange after being baked for 60 minutes. Comparative Example 3 was slightly oxidized and discolored to light orange after being baked at 230°C for 30 minutes, but was moderately oxidized and discolored to purple after being baked for 60 minutes. Figure 2 , Figure 3 shown.
[0056] It can be seen that when the additive does not contain either ytterbium ions or butylated hydroxytoluene, the oxidation resistance of the copper foil will deteriorate, and when neither of these two components is contained, the oxidation resistance will further deteriorate. When the butylated hydroxytoluene content exceeds the content range, the oxidation resistance of the copper foil will also deteriorate. This is because when the amount of butylated hydroxytoluene added is too much, the antioxidant free radicals distributed on the surface will agglomerate and reduce their efficiency in adsorbing oxygen molecules.
[0057] In summary, in the process of electrolytic copper foil, by adding the additive of the present invention into the electrolyte, the oxidation resistance of the ultra-thin copper foil can be improved.
Claims
1. An additive capable of improving the oxidation resistance of ultra-thin copper foil, characterized in that: The additives include ytterbium ions, butylated hydroxytoluene, polyethylene glycol and a brightener.
2. The additive for improving the oxidation resistance of ultra-thin copper foil according to claim 1, characterized in that: The ytterbium ions include one or more of ytterbium sulfate, ytterbium nitrate or other salts containing ytterbium ions.
3. The additive for improving the oxidation resistance of ultra-thin copper foil according to claim 1, characterized in that: The polyethylene glycol includes one or more of polyethylene glycol 1000, polyethylene glycol 2000 or polyethylene glycols with other molecular weights.
4. The additive for improving the oxidation resistance of ultra-thin copper foil according to claim 1, characterized in that: The brightener includes one or more of sodium polydisulfide propane sulfonate, sodium isothiourea propane sulfonate, and sodium imidazole dithiocarboxylate propane sulfonate.
5. The additive for improving the oxidation resistance of ultra-thin copper foil according to claim 1, characterized in that: The ytterbium ion concentration is 2.0-5.0 mg / L, and the butylated hydroxytoluene concentration is 10.0-20.0 mg / L.
6. The additive for improving the oxidation resistance of ultra-thin copper foil according to claim 5, characterized in that: The concentration of the polyethylene glycol is 2.0-20.0 mg / L, and the concentration of the brightener is 5.0-20.0 mg / L.
7. A copper foil produced using the additive according to any one of claims 1 to 6, characterized in that: The copper foil has no oxidative discoloration when placed at 85° C. and 85% relative humidity for 120 hours, and has no oxidative discoloration after being baked at 230° C. for 60 minutes.
8. The copper foil according to claim 7, characterized in that: The steps include: (1) Preparation of additives; (2) adding the additive to the copper sulfate electrolyte, mixing and stirring evenly, and then electrolyzing and producing foil; (3) The obtained copper foil is passivated with chromic anhydride passivation solution, and then dried and peeled to obtain the finished copper foil.
9. The copper foil according to claim 8, characterized in that: The copper ion concentration in the copper sulfate electrolyte in step (2) is controlled at 80-110 g / L, the acid concentration is controlled at 90-130 g / L, the chloride ion concentration is controlled at 5-20 mg / L, the electrolyte temperature is controlled at 45-60° C., and the current density is controlled at 40-60 A / dm 2 .
10. The copper foil according to claim 8, characterized in that: The test method for the oxidation resistance of the copper foil includes a double 85 oxidation resistance test and a high temperature oxidation resistance test.
Citation Information
Patent Citations
A method for electrodeposition of copper foil and composite copper foil materials
CN111101179B
Ultrathin copper foil with high oxidation resistance and method for improving oxidation resistance of ultrathin copper foil
CN118147638A
Rare earth Ce ion modified additive for high-strength ultrathin electrolytic copper foil material
CN118407095A
Cited By
Electrocoppering solution for ceramic packaging substrate and use method of electrocoppering solution
CN120844160A
Electroplating copper solution for ceramic package substrate and method of use thereof
CN120844160B